New Border Studies On Israel/Palestine: Review of Two Books - Meier, Daniel (Borders in Globalization Review, 2021)
Review essay on The Politics of Maps: Cartographic Constructions of Israel/Palestine by Christine Leuenberger & Izhak Schnell and Penser la Palestine en réseaux by Véronique Bontemps, Nicolas Dot-Pouillard, Jalal al-Husseini & Abaher al-Sakka.